Exosomes in Dermatology: Emerging Roles in Skin Health and Disease - Salman Bin Dayel; Ramadan S. Hussein (Pharmaceutics)
Background/Objectives: Exosomes, nanosized vesicles secreted by diverse cell types, have emerged as critical mediators of intercellular communication, tissue repair, and disease pathogenesis. Their roles in dermatology are increasingly recognized, influencing skin health and the progression of various dermatological conditions. This review aims to explore the biogenesis, composition, and mechanisms of exosome uptake in skin cells and their implications in dermatological research and clinical practice. Methods: A comprehensive review of the existing literature was conducted to elucidate the biological composition of exosomes, their roles in skin homeostasis, and their involvement in processes, such as wound healing, tissue regeneration, and barrier function maintenance. This review also examined the diagnostic and therapeutic potential of exosomes in conditions such as psoriasis, eczema, acne, and skin cancer. Results: Exosomes were found to contain intricate compositions, including proteins, lipids, nucleic acids, and bioactive molecules, crucial for maintaining skin homeostasis. They demonstrated significant roles in modulating wound healing and skin regeneration. Emerging evidence highlights their involvement in dermatological conditions and their potential as diagnostic biomarkers and therapeutic agents. Exosome-based approaches hold promise for advancing disease management, although challenges remain in translating these findings into clinical applications. Conclusions: Exosomes represent a promising frontier in dermatology, with the potential to revolutionize the understanding, diagnosis, and treatment of skin-related disorders. Despite the challenges, their complexity and versatility underscore their potential in developing personalized skin health strategies. Further research is warranted to address the existing gaps and harness the full therapeutic potential of exosomes in dermatological applications.